Actin blobs prefigure dendrite branching sites. - Nithianandam, V.; Chien, C.T. (Journal of Cell Biology, 2018)
The actin cytoskeleton provides structural stability and adaptability to the cell. Neuronal dendrites frequently undergo morphological changes by emanating, elongating, and withdrawing branches. However, the knowledge about actin dynamics in dendrites during these processes is limited. By performing in vivo imaging of F-actin markers, we found that F-actin was highly dynamic and heterogeneously distributed in dendritic shafts with enrichment at terminal dendrites. A dynamic F-actin population that we named actin blobs propagated bidirectionally at an average velocity of 1 µm/min. Interestingly, these actin blobs stalled at sites where new dendrites would branch out in minutes. Overstabilization of F-actin by the G15S mutant abolished actin blobs and dendrite branching. We identified the F-actinsevering protein Tsr/cofilin as a regulator of dynamic actin blobs and branching activity. Hence, actin blob localization at future branching sites represents a dendrite-branching mechanism to account for highly diversified dendritic morphology.